Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1057/palgrave.jphp.3190031
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Cigarette Smoking in the Workplace in Taiwan: Opportunities and Challenges

Abstract: Cigarette smoking is one of the most serious health problems in Taiwan. Although the Taiwanese government passed a Tobacco Hazard Control Act in 1997, it is not fully applicable to the workplace. The purpose of the study was to review workplace smoking prevalence and policies, and to discuss the opportunities and challenges of implementing workplace smoking policies in Taiwan. Results show that smoking prevalence in the workplace in Taiwan is high, particularly among males, ranging from 38 to 68%. More than 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Contrary to the observation in the US and Taiwan, large and blue-collar companies in the present study were more likely to promote SC [ 2 , 4 , 13 ]. Large companies are led by written regulations and more likely to comply with the smoke-free workplace ordinance while small/medium companies were more likely to rely on informal communication and to respect individual freedom of smoking [ 2 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the observation in the US and Taiwan, large and blue-collar companies in the present study were more likely to promote SC [ 2 , 4 , 13 ]. Large companies are led by written regulations and more likely to comply with the smoke-free workplace ordinance while small/medium companies were more likely to rely on informal communication and to respect individual freedom of smoking [ 2 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similar study is scarce in Asian countries. One study has shown that less than half of the companies in Taiwan adopted smoke-free policy [ 4 ]. Regarding the low adoption rate, employers expressed their concerns on the lack of perceived responsibility for maintaining a smoke-free workplace, the insufficient knowledge on the impact of smoking on the company and employees, and the worries about undermining employee’s morale and customer’s satisfaction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Associated implications to policy issues have been addressed elsewhere. 28 The loss of productivity and costs associated with worker replacement due to smoking related premature mortality were not included in this paper. While reducing smoking will clearly lead to a reduction in premature mortality and increased productivity, these will not happen immediately.…”
Section: Discussionmentioning
confidence: 99%
“…ETS is a significant threat to public health, associated with various cancers, cardiovascular disease, and respiratory impairment. [1][2][3] Acknowledging the scientific evidence of the benefits of smoke-free environments, the number of people covered by smoke-free laws has increased exponentially in recent years achieving significant gains for public health in Ireland, Cyprus, UK, many US states, and most recently Greece. [4][5][6][7][8] Research has indicated that people become less tolerant of exposure to ETS as they become accustomed to smoke-free environments.…”
Section: Introductionmentioning
confidence: 99%